2016
DOI: 10.1177/0956462415610679
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infection diagnoses among Hispanic immigrant and migrant men who have sex with men in the United States

Abstract: Background: Hispanic immigrant/migrant men who have sex with men should be at higher risk for sexually transmitted disease/human immunodeficiency virus (STD/HIV) infections given individual-level factors associated with the migration process that have been theorised to increase susceptibility to STD/HIV infections among migrant populations, yet relatively little is known if these individual level factors are actually associated with a sexually transmitted disease infection among this population. Methods: Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The most frequently diagnosed STI, in both immigrant and native populations, was HPV infection. This is consistent with a study on STIs conducted in the same region, Andalusia [20], in which HPV infection was the most frequent infection as early as 2009. With respect to other diagnoses, such as hepatitis B and syphilis, also reported in other studies, the results are consistent with another study [21] that reports a higher prevalence of hepatitis B in the immigrant population compared to the native population.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequently diagnosed STI, in both immigrant and native populations, was HPV infection. This is consistent with a study on STIs conducted in the same region, Andalusia [20], in which HPV infection was the most frequent infection as early as 2009. With respect to other diagnoses, such as hepatitis B and syphilis, also reported in other studies, the results are consistent with another study [21] that reports a higher prevalence of hepatitis B in the immigrant population compared to the native population.…”
Section: Discussionsupporting
confidence: 92%
“…Transmission network analysis can provide public health officials with high-resolution information about transmission and drug resistance dynamics at global [20], national [21], and subnational [22,23] levels. These data have been used to identify growing transmission clusters of concern, monitor transmission of antiretroviral drug resistance, prioritize high-risk groups for prevention efforts, and aid epidemiologic investigations [24][25][26][27]. While transmission network analysis is a well-established complement to tuberculosis contact-tracing investigations [16,28,29], it is a relatively new approach for HIV surveillance and outbreak investigation.…”
mentioning
confidence: 99%
“…In Mexico, a study showed that the prevalence of STIs in female sex workers was for syphilis 7.8% (range 0% -17.2%), chlamydia 15.3% (range 5.7% -32.2%), gonorrhea 2.9% (range 0% -13.8%) and any HIV / STI 23% (range 9.9% -46%) [7]. The presence of concurrent infections due to any of these bacteria is a risk factor for HIV [8,9]; This is because, by breaking the epithelial barrier of the genital tract, this facilitates the access of the virus to the target cells under the epithelial barrier [8,10]. Alternatively, people infected with HIV are more susceptible to other STIs, since they are immunosuppressed and less able to develop an adequate response to sexually transmitted pathogens [8,11].…”
Section: Introductionmentioning
confidence: 99%